Pseudonocardia abyssalis sp. nov. and Pseudonocardia oceani sp. nov., two novel actinomycetes isolated from the deep Southern Ocean. Issue 9 (28th September 2021) - Parra, Jonathan; Soldatou, Sylvia; Rooney, Liam M.; Duncan, Katherine R.
Abstract : The actinomycetes strains KRD168 T and KRD185 T were isolated from sediments collected from the deep Southern Ocean and, in this work, they are described as representing two novel species of the genus Pseudonocardia through a polyphasic approach. Despite sharing >99 % 16S rRNA gene sequence similarity with other members of the genus, comparative genomic analysis allowed species delimitation based on average nucleotide identity and digital DNA–DNA hybridization. The KRD168 T genome is characterized by a size of 6.31 Mbp and a G+C content of 73.44 mol%, while the KRD185 T genome has a size of 6.82 Mbp and a G+C content of 73.98 mol%. Both strains contain meso -diaminopimelic acid as the diagnostic diamino acid, glucose as the major whole-cell sugar, MK-8(H4 ) as a major menaquinone and iso -branched hexadecanoic acid as a major fatty acid. Biochemical and fatty acid analyses also revealed differences between these strains and their phylogenetic neighbours, supporting their status as distinct species. The names Pseudonocardia abyssalis sp. nov. (type strain KRD168 T =DSM 111918 T =NCIMB 15270 T ) and Pseudonocardia oceani (type strain KRD185 T =DSM 111919 T =NCIMB 15269 T ) are proposed.